Meningkatkan Hasil Belajar Siswa dengan Menggunakan Pendekatan PBL Berbantuan Quizizz Pembelajaran Pak Materi Maria dan Elisabeth SDI Meti Manggarai NTT - Thomas Aquinas Pakas; Sugiyana Sugiyana; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
The problem faced by grade V students of SDI Meti is the low learning outcomes achieved. This is because teachers have not implemented/used student-oriented methods in the learning process. So far, the learning approach applied by teachers still uses monotonous lectures, so that the achievement of student learning outcomes is very low. This happens because of the lack of teacher innovations. The purpose of this study is to find out student learning outcomes, improve student learning outcomes and evaluate student learning with the PBL approach using Quizizz. This class action research was carried out in four stages, namely planning, implementation, evaluation, and reflection, with 16 students in class V. The research was carried out in two cycles with a Problem based learning (PBL) approach/model to improve affective aspects in the learning process. The results showed that there was an increase in affective aspects from cycle 1 to cycle 2 by 80%. The results of the cognitive aspect test of the material of God's Call to Mary showed that there was an increase in the average score of cycle 1 by 35% to 45% in cycle 2. The results of the reflection recommend that there needs to be assistance in the affective aspect for students so that it can improve student learning outcomes. Conclusion: The results of the study show that in cycle I, student learning outcomes are still low. However, in cycle II, students showed a significant improvement in learning outcomes. This shows that learning with a PBL approach and focusing on the independent dimension can improve student learning outcomes.